Champagne: the challenge of value co-creation through regional brands. Issue 2 (4th June 2019) - Kunc, Martin; Menival, David; Charters, Steve
Abstract : Purpose: The traditional view of the process of value creation suggests that it occurs inside the firm through its activities or resources. However, there are special cases where firms create value using external shared resources, e.g. a territorial brand. The purpose of this study is to demonstrate how the combination of both internal and external resources co-create value in wine regions. Design/methodology/approach: An in-depth case study of nine firms covering different co-creation processes in Champagne, France. The selection of interviews was designed to cover the diversity of firms within the area with different market positioning. Most firms in the region have been selling champagne for more than 50 years, so they have established long-standing relationships with their markets. Findings: While there is only one value, Champagne, firms create many different values based on owners' perceptions with diverse effects on the process of value co-creation in the territorial brand. Some firms have strategies which could deteriorate the value of shared resource. This threat needs institutional changes with unknown consequences on the territorial brand. Research limitations/implications: The research only involved one case study with a highly developed territorial brand system. There are multiple wine regions that have considered managing either implicitly or explicitly their shared strategic resources (e.g. a territorial brand). Consequently, the findings may not be applicable to all wine regions but it can provide a "gold standard" for regions and wineries that do not realize the impact that their value creation actions can have on the wine region. Practical implications: Collective management of shared strategic resources, such as a territorial brand, can be a powerful action to sustain competitive advantage rather than individual actions to develop individual brands. However, it can work only with an institutional organization managing the collective process. Originality/value: The paper offers lessons from a comprehensive and well-known case study where resource bundles co-create value with a territorial brand.